A text messaging intervention and quality of life in adolescents with solid organ transplants. (9th February 2022) - Rathgeber, Steven L.; Hutchison, Sarah M.; De Souza, Astrid‐Marie; Lester, Richard; Blydt‐Hansen, Tom; Human, Derek G.; Guttman, Orlee; Oberlander, Tim F.; Armstrong, Kathryn R.
Abstract: Background: Facilitating communication between adolescents and HCP outside of appointments may enhance patient experience and outcomes. The purpose of this study was to determine whether SMS enhances the healthcare experience, QoL, and medication adherence in adolescent SOT patients. Methods: This was a prospective observational study of an SMS platform (WelTel Inc) for SOT patients aged 12–19 years. QoL was assessed before and after using the PedsQL™ Transplant Module. Medication adherence was assessed with the frequency of therapeutic tacrolimus levels and variation based on control chart analysis. Patient experience and engagement was evaluated with surveys, response rate to messages, and number of clinical conversations (>2 messages). Results: Twenty‐three patients were included (median age 15.7 years (IQR 13.6–17.1)). Median intervention duration was 13.5 months (range 4.0–16.7 months). There was a 68% response rate (742/1095) with 375 clinical conversations. The majority of patients reported the intervention provided a positive outlook on their health (17/23), was useful (18/23), and improved their connection to HCPs (17/23). Following the intervention, there was no significant difference in the median scaled QoL scores (pre‐intervention: 81 (IQR 76.5–93.3), post‐intervention: 78 (IQR 76–93); p = .37), mean percentage of therapeutic tacrolimus levels (pre‐intervention: 52 ± 25%, post‐intervention: 65 ± 17%; p = .07), or variation on control chart analysis of tacrolimus levels. Conclusions: The WelTel messaging platform provided supplemental clinical care for a group of adolescent SOT patients that enhanced their healthcare experience. Patient QoL and adherence were unchanged following the intervention and remained at a high level.